An experiment result based on adaptive neuro-fuzzy inference system for stock price - Cuong, Bui Cong; Chien, Pham Van (Journal of Computer Science and Cybernetics, 2012)
In the last years, the financial markets around the world have been modified by the rapid development of advance systems. The acquisition of high-frequency data in real times has developed new fields like neuro-fuzzy systems for forcasting problems, renewing also the interest in the forcasting of financial and stock market indexes. In this paper, we present an experiment result based on Adaptive Neuro-Fuzzy Inference System with a new computing procedure for stock price prediction.